Polyculture of Osteobrama belangeri with major carps in pen enclosures in Takmu lake of Manipur - Yengkokpam, S; Debnath, D; Bhattacharya, B K; Yadav, A K; Das, P; Sarma, K K (Journal of the Inland Fisheries Society of India, 2021)
Feasibility of culturing pengba (Osteobrama belangeri) as a candidate species in polyculture along with other carps in the net-pen enclosure was studied in Takmu Lake, Manipur. A net-pen measuring 0.1 ha was constructed using a nylon net supported by bamboo poles. The average length and weight of stocked fingerlings (@5 no. m-2 ) were as follows: pengba (9.4±0.26 cm, 10.6±0.33 g), Labeo catla (16.1±0.88 cm, 39.0±2.19 g), Labeo rohita (14.8±0.15 cm, 38.6±2.19 g), Cirrhinus mrigala (16.2±0.32 cm, 41.9±2.17 g), Hypophthalmichthys molitrix (14.2±0.64 cm, 30.3±1.45 g), Ctenopharyngodon idella (22.4±0.29 cm, 115.2±4.15 g) and Cyprinus carpio (14.8±0.81 cm, 55.1±1.39 g). Fishes were fed with pelleted feed having 23.4% crude protein @ 5% of body weight twice-a-day for 180 days. Highest growth, in terms of weight gain % and specific growth rate, was recorded in pengba followed by C. idella, L. catla, C. mrigala, L. rohita, C. carpio and H. molitrix. The pen aquaculture system was found to be economically viable with a benefit-cost ratio of 1.37. The present study established that netpen aquaculture of pengba along with other carps is economically viable and technically feasible in floodplain wetlands of Manipur. Key words: Pen aquaculture; Takmu Lake; Polyculture; Osteobrama belangeri, Major carps; Exotic carps